1971
DOI: 10.1071/ar9710159
|View full text |Cite
|
Sign up to set email alerts
|

Variations between and within breeds of cattle in resistance to field infestations of the cattle tick (Boophilus microplus)

Abstract: Maturing female ticks were counted in herds of Brahman x British, Africander x British, and British breed (Shorthorn x Hereford) cattle run together. About 3000 counts were made on over 1000 cattle. The Zebu crossbreds on average carried two-fifths the number of ticks carried by the British cattle, though in some herds the difference was greater, and it tended to be greater in females than in males, in summer than in winter, and in F2 than in F3 animals. Brahman cross and Africander cross cattle did not differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
5

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 0 publications
3
41
0
5
Order By: Relevance
“…Typically, Bos indicus animals are more resistant to ticks than are Bos taurus, although some variation occurs among and within breeds (Seifert, 1971). Genetic variations in tick resistance result from differences in a variety of mechanisms that are not fully understood, although the involvement of genes related to the immune system appears to be undeniable (Regitano and Prayaga, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Bos indicus animals are more resistant to ticks than are Bos taurus, although some variation occurs among and within breeds (Seifert, 1971). Genetic variations in tick resistance result from differences in a variety of mechanisms that are not fully understood, although the involvement of genes related to the immune system appears to be undeniable (Regitano and Prayaga, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bos indicus cattle breeds are more resistant to R. microplus than are Bos taurus breeds, although considerable variation in resistance occurs between and within breeds (37,45). Although innate immunity arising from genetic differences between B. indicus and B. taurus breeds forms the basis of whether an animal will be resistant to tick infestation, host resistance is considered to be predominantly an acquired trait because the higher level of resistance seen in B. indicus becomes apparent only following a period of initial susceptibility to primary infestation (15,44).…”
mentioning
confidence: 99%
“…Although innate immunity arising from genetic differences between B. indicus and B. taurus breeds forms the basis of whether an animal will be resistant to tick infestation, host resistance is considered to be predominantly an acquired trait because the higher level of resistance seen in B. indicus becomes apparent only following a period of initial susceptibility to primary infestation (15,44). Host resistance to tick infestation is heritable, with a rate estimated to be between 39% and 49% for British breed animals (45) and as high as 82% in Africander and Brahman (B. indicus) crossbred animals (37). Since these initial studies, it has been shown that the resistance status of both B. taurus and B. indicus breeds can be improved by selection for increased tick resistance, as demonstrated by a breeding program that has resulted in a highly tick-resistant line of Hereford ϫ Shorthorn (B. taurus) cattle, now known as the Belmont Adaptaur (9,25).…”
mentioning
confidence: 99%
“…Overall, we found a significant association between the number of ticks and the sex and mass of cattle, with more parasites found on males, whereas we detected no association between parasites and the age of cattle. In many cattle species, males have more ticks than females (Seifert 1971;Martinez et al 2006;Dudek et al 2016), likely because of differences in hormone levels. This may also simply be due to the weight of the animals; those that are bigger capture more ticks, and males are generally larger than females.…”
Section: Discussionmentioning
confidence: 99%